Beyond the text unpacking the reportage of selected gender-sensitive front-page banner photographs from 2019–2021 of Inquirer, Manila Bulletin, and Philippine Star - Simba, Glecelyn O.
Photographs hold as much power as the texts and captions—if not more. An image can speak and tell a story on its own; at the same time, photos also invite multiple interpretations. Beyond the audience reception, the behind-the-scenes motivations and editing are things the audience often overlooks. Given the power an image holds, how can a photojournalist accurately and ethically frame gender news coverage? Anchored in De Vreese’s frame-building theory and Semetko and Valkenburg’s five gender news frames, this study examined front-page banner photos of selected Philippine broadsheets to identify the dominant gender frames employed by photojournalists and their newsrooms. It further analyzed the languages of the image or visual elements usually attached to gender-sensitive photos and assessed whether these photos adhered to the Photojournalists’ Center of the Philippines Code of Ethics. The findings revealed that the majority of the gender-sensitive banner photos were married to “Human Interest Frames,” a storytelling style intended to evoke emotional engagement. Aligned to this frame, mood, emotion, and impact were the elements commonly used in the photos. While several photos conform to the ethical standards, some do not—underscoring the importance of developing or revisiting gender-sensitive guidelines to ensure ethical reporting.